Caracterização populacional e descrição do manejo de gatos errantes no Parque Municipal Américo Renné Giannetti, Belo Horizonte, Minas Gerais - Paloma Carla Fonte Boa Carvalho (2018)
Cats are becoming the most popular companion animal; however, they are involved in zoonosis transmission, such as rabies. Between 2008 and 2014, four bats were identified as positive for rabies in the Parque Municipal Américo René Giannetti (PqMARG), a public space that shelters wild animals and stray cat colonies. The abundant presence of domestic cats, a specie that presents hunting habits, associated with the presence of bats positive for rabies demonstrates a complex link between the urban and the wild cycles of rabies transmission within the limits of the PqMARG and its surroundings. This scenario illustrates the need to implement systematic actions for preventing, monitoring and controlling rabies in this environment, including capture, reproductive sterilization, identification and rabies vaccination of these animals. Furthermore, the apparent increase in the number of cat colonies indicates the need of studies characterizing the population dynamics, the behavior, and the interactions of the feline population habiting the PqMARG. The aim of the present study was to characterize and evaluate the management of the population of cats of the PqMARG, as well as estimate the population size, identify the colonies, establish spatial distribution and colonies density, and evaluation of adoptions. Moreover, the cats were captured, identified through microchip implementation and ear marking, scanned for clinical and behavioral characteristics. The captures occurred every Monday, and observations were on Mondays and Thursday. Cats were properly restrained and brought to the CCZ-PBH by public servers. The cats were then submitted to neuter surgeries, vaccination, identification, and a form with the animals information, such as sex, age, capture method and site, and final destine, was filled between 2015 and 2017. Altogether, 401 cats were captured; however, 11 (2,7%) were found dead, but were considered negative for rabies. The majority of the alive animals captured were female (215-55,1%), and the proportion found was 1,2 females for each male. Regarding age, 22% (n=86) of the animals were kittens, 18,5% (n=72) were young, and 59,5% (n=232) were adults. The captures using the puçá corresponded to 58,5% (n=228) of the total, while 38,2% (n=149) of animals were captured with bare hands, and 3,1% (n=12) with a trap. Eight places were identified as being the ones were most of the animals were captured, corresponding to 85,3% (n=322) of all captures. Reproductive sterilization surgery was performed in 74,1% (n=289) of the animals; 50 (12,8%) cats were already neutered, and the rest of the cats, 13,1% (n=62), were not eligible for the procedure due to age of clinical condition. Concerning the final destiny of the cars, 71,3% (n=286) returned to the PqMARG, 16,7% (n=97) were adopted, 7% (n=28) perished, and 2% (n=8) were euthanized. In the first period of observation, from October to November 2016, 9 observations were made at the PqMARG. For estimating cat population size, two different methods were employed: using the direct count method, we obtained a total of 149 cats; however, with the Jolly-Seber method, that uses the marking-recapture data, the total count was of 77 cats. The second period of observation occurred from October to November 2017, and 15 observations were made at the PqMARG. Cat population was estimated in 228 cats by the direct count method, being 39 (17,1%) of them cats from the first observation. With the Jolly-Seber method, the population was estimated in 283 cats. Characterizing the population and the management of the cats from the PqMARG, along with other control measures, are fundamental to support health programs, aiming to mitigate the risks of occurrence of zoonotic diseases, such as rabies, and to provide improvement of humans and animals welfare.